Listening from Silence: Inner Composure and Engagement - Waks, Leonard J. (Paideusis, 2008)
The Indian-America philosopher Sri Chinmoy Ghose has distinguished between outer silence, inner silence, and innermost silence. In this paper I explore these distinctions and their educational relevance. My main conclusions are that (a) a deep inner silence, undistracted by questions or other thoughts, is at the root of one paradigm kind of good listening in education, and (b) what Chinmoy refers to as “innermost silence” is the moral virtue of receptivity to others that sustains inner silence, even under challenging conditions, a virtue of importance in teaching and in learning from others.